EXPLORING SELF-CONCEPT AND COMMUNICATION STYLES AMONG COSPLAYERS IN SOCIAL CONTEXTS - Arifiah, Adinda (Yayasan Nuraini Ibrahim Mandiri, 2025)
This study aims to uncover how cosplayers in Balikpapan, East Kalimantan, construct their self-identity and communication style through cosplay practices. Using a qualitative phenomenological approach, data were collected through in-depth interviews with ten active cosplayers for at least one year, participant observation at various cosplay events, and literature studies on self-concept, identity formation, and symbolic interaction theories (Harris, 2022; Taylor & Dawson, 2021; Smith & Wallace, 2023). Thematic analysis of interview data and field notes identified four main findings: (1) identity negotiation through cosplay names and chosen characters; (2) self-transformation and increased self-confidence since the first cosplay experience; (3) development of self-concept strengthened by community appreciation; and (4) a more open communication style within the community but limited by stigma outside the community. These findings suggest that cosplay is not just entertainment, but a transformative medium for self-exploration, social skill development, and creative network formation. Despite the challenges of social stigma, participation in cosplay has been shown to increase self-confidence, communication skills, and facilitate professional opportunities in the creative industry. Further research is recommended to explore the long-term psychological impacts of cosplay in various cultural contexts. Keywords: Cosplay, Self-Identity, Communication Style, Phenomenology, Cosplay Community, Symbolic Interaction